Petroleum products biodegradation profile similarity evaluated by F test comparison of weekly CO2 production - Bidoia, E. D. [UNESP]; Montagnolli, R. N. [UNESP]; Lopes, P. R. M. [UNESP]; MendezVilas, A. (World Scientific Publ Co Pte Ltd, 2012)
Strategies applied to bioremediation contaminated environments are necessary to identify limitations towards biodegradation and to predict remediation performance and thereby rule out technologies that may be inappropriate for the clean-up of the substances of concern. Respirometry applied to bioremediation offers a series of advantages for obtaining CO2 production data when compared to other procedures. It was possible to determinate information regarding the atmosphere's CO2 concentration inside a respirometer containing petroleum products. Afterwards, the CO2 data obtained underwent an in depth statistical analysis by F test. There are some noticeable biodegradation similarity among some substances, such as weathered motor oil and gasoline. Such data provides reliability when revealing important information about how the biodegradation processes happens in those residual oils.
Keywords: F test; bioremediation; respirometry